Breaking the poverty code : an integrative approach to measuring multidimensional poverty in Mexico - Guillen-Ferna, Yedith Betzabe (Emerald points., 2023)
A lack of socially determined needs, such as nourishment, education, and healthcare, can become deprivation indicators that are used to measure poverty. Breaking the Poverty Code recognizes that any mismeasurement may provide inaccurate information to policymakers about the extent of poverty in the population, potentially inhibiting the success of policy initiatives moving forward. Advocating for a more objective measurement, Yedith Betzabé Guillén-Fernández reinvents how poverty is presented and defined by exploring methods currently employed by CONEVAL, the institution in charge of applying the official methodology for multidimensional poverty in Mexico. With this context in mind, Yedith argues for the implementation of the Consensual approach to inform the Social Rights-based approach as a way to update criteria for living standards. Calling for a more holistic conception of poverty that accounts for evolving socioeconomic and technological needs, chapters highlight both British and Latin American scholarship to emphasize the fluidity that must be taken into account when defining poverty. Transcending the Mexican context, this book presents critical sociological observations that fuse the importance of statistical data with the lived realities of impoverished people everywhere.